Why Is Virtual Reality Interesting for Philosophers? - Metzinger, Thomas K. (Frontiers in Robotics and AI, 2018)
This article explores promising points of contact between philosophy and the expanding field of virtual reality research. Aiming at an interdisciplinary audience, it proposes a series of new research targets by presenting a range of concrete examples characterized by high theoretical relevance and heuristic fecundity. Among these examples are conscious experience itself, “Bayesian” and social VR, amnestic re-embodiment, merging human-controlled avatars and virtual agents, virtual ego-dissolution, controlling the reality/virtuality continuum, the confluence of VR and artificial intelligence (AI) as well as of VR and functional magnetic resonance imaging (fMRI), VR-based social hallucinations and the emergence of a virtual Lebenswelt, religious faith and practical phenomenology. Hopefully, these examples can serve as first proposals for intensified future interaction and mark out some potential new directions for research.